Cocaine affects foraging behaviour and biogenic amine modulated behavioural reflexes in honey bees - Eirik Søvik; Naïla Even; Catherine W. Radford; Andrew B. Barron (PeerJ, 2014)
In humans and other mammals, drugs of abuse alter the function of biogenic amine pathways in the brain leading to the subjective experience of reward and euphoria. Biogenic amine pathways are involved in reward processing across diverse animal phyla, however whether cocaine acts on these neurochemical pathways to cause similar rewarding behavioural effects in animal phyla other than mammals is unclear. Previously, it has been shown that bees are more likely to dance (a signal of perceived reward) when returning from a sucrose feeder after cocaine treatment. Here we examined more broadly whether cocaine altered reward-related behaviour, and biogenic amine modulated behavioural responses in bees. Bees developed a preference for locations at which they received cocaine, and when foraging at low quality sucrose feeders increase their foraging rate in response to cocaine treatment. Cocaine also increased reflexive proboscis extension to sucrose, and sting extension to electric shock. Both of these simple reflexes are modulated by biogenic amines. This shows that systemic cocaine treatment alters behavioural responses that are modulated by biogenic amines in insects. Since insect reward responses involve both octopamine and dopamine signalling, we conclude that cocaine treatment altered diverse reward-related aspects of behaviour in bees. We discuss the implications of these results for understanding the ecology of cocaine as a plant defence compound. Our findings further validate the honey bee as a model system for understanding the behavioural impacts of cocaine, and potentially other drugs of abuse.